The Effect of Telmisartan and Metformin on Insulin Resistance in Metabolic Syndrome Patients with Insulin Therapy - Oktariani, Siswi; Pramono, Raden Bowo; Sinorita, Hemi (Acta Interna The Journal of Internal Medicine, 2014)
ABSTRACTBackground: Recommendations for therapy insulin resistance are metformin and thiazolidindion. Side effects of thiazolidindion due to peripheral edema occurs to 2-5% and increased 5-15% when combined with insulin therapy. Telmisartan, an angiotensin receptor blocker, has anti-hypertensive effects and improve insulin resistance. Telmisartan effect on peroxisome proliferator activated receptor Î³ agonist and has the same structure of the group thiazolidindion, pioglitazone. The research objective was to determine the effects of telmisartan and metformin on insulin resistance in metabolic syndrome patients with insulin therapy.Methods: This study used a before-after design. The study was conducted in the internal medicine clinic of the endocrinology department of Dr. Sardjito Hospital Yogyakarta. Subjects were patients who met the diagnosis of metabolic syndrome based on the IDF 2005, hypertension and receive insulin therapy. Subjects given metformin and telmisartan therapy for 12 weeks. Subjects examined HOMA IR before and after treatment. The average decrease in HOMA IR was tested by paired t test or Wilcoxon test. P value <0.05 was considered signifi cant.Result: The total sample were 27 subjects. Data analysis was performed on 11 subjects. Fasting blood glucose before and after treatment was signifi cantly decreased (p<0.001) whereas the fasting insulin levels increased. HOMA IR was signifi cantly decreased after treatment p = 0.004 (5.79 â 20.26), CI 95%.Conclusion: this study found insulin resistance decreased signifi cantly in patients with the metabolic syndrome of insulin therapy who received metformin and telmisartan.Keywords : metabolic syndrome, insulin therapy, metformin, telmisartan, HOMA IR